Carlos Eduardo Zavaleta: approach and proposed periodisation of his critical reflection - Orihuela Oropeza, Lourdes Melisse (2024)
Carlos Eduardo Zavaleta (1928-2011) was a Peruvian writer, translator, essayist and chancellor, known mainly for his membership of the Generation of the 1950s. The most outstanding aspect of Zavaleta and the one most studied by critics has been his facet as a storyteller, especially as a short-story writer, in which he developed extensively throughout most of his life. However, his facet as an essayist has been little developed, and for this reason, this paper aims to review and periodise C. E. Zavaleta’s production of essays and articles in four main stages. The first, formative (1948-1952), in which he focused on reviewing and commenting on translations of foreign books. The second, the dissemination of foreign writers (1953-1973), in which his publications revolved around promoting the new techniques and style of North American and European writers; likewise, this stage also included articles on the dissemination of Peruvian literature to the world. In the third period, the Generation of the 1950s (1974-2000), Zavaleta studies and disseminates the narrators of his generation, relating them to the influences of the foreign writers mentioned above. In the fourth and last period, the miscellaneous (2001-2012), he develops with equal proportion the three main concerns of the writer: the influence of foreign writers, the generation of the 1950s and the dissemination of Peruvian literature.